The Influence of Motivation and Work Environment on Employee Performance at PT. Matahari Department Store, Tbk in Sampit - M. Thamrin Noor; Dita Yulita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The title of this research is the Influence of Motivation and Work Environment on Employee Performance at PT. Matahari Department Store, Tbk in Sampit. The sampling technique used is saturated sampling or sampling technique where all of the population used as a sample of 50 people then said as respondents. The Data in the test by using validity test, reliability test, test the hypothesis and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and analyst determination. Based on the results of the hypothesis test in this research is t-test for veriabel Motivation (X1) that tcount > ttable (8,246 > 2,01174) and a significant level of 0.000 < 0.05, then H0 is rejected and Ha is accepted, meaning that there is significant influence between Motivation On Employee Performance. As for the t-Test for the variables of the Work Environment (X2) that tcount > ttable (4,039 > 2,01174) and a significant level of 0.000 < 0.05, then H0 is rejected and Ha accepted which means that there is significant influence between Work Environment on Employee Performance. Then to Test-F that Fcount > Ftable (58,670 > 3,20) and a significant level of 0,000 < 0,05 means simultaneously Motivation and Work Environment affect the Performance of Employees at PT. Matahari Department Store, Tbk in Sampit. Numbers R by 0,845 shows the relationship/correlation between the Performance of Employees with the independent variables is very strong (Significant). R square (R2) at 0.714 that 71,4% variable Employee Performance (Y) can be explained by the Motivation variable (X1) and Work Environment (X2). While the rest of 28.6% is influenced by other Variables that are not included in this study such as Compensation, Organizational Culture, Work Climate, Leadership Style, and so forth.